Mega-regional trade agreements : CETA, TTIP, and TiSA : new orientations for EU external economic relations - Griller, Stefan; Obwexer, Walter; Vranes, Erich (Oxford : Oxford University Press, 2017)
This volume brings together leading experts in the field of international economic law to address the legal complexities of the TTIP, CETA, and TISA treaties and provide an explanation of their core principles. It also addresses the controversies surrounding the treaties, including their regulatory ambition and insufficient transparency.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 18, 2017).
Keywords: European Union countries -- Commercial treaties; European Union countries -- Foreign economic relations; Commercial treaties; European Union; Law; International law